Research on Anti-seepage Curtain Layout of a Deep Foundation Pit near the Levee - WANG Xuehong; LIU Xiaoqing; ZHANG Hui; WANG Xin; YAO Lu (Renmin Zhujiang)
A deep foundation pit project is located in the east of the levee at Yangzhou section of the Grand Canal.There are silt soil and silt sand layers in the bottom of the foundation pit within excavation depth,which is prone to seepage accidents,threatening the safety of the levee.Based on MIDAS GTS,this paper establishes a three-dimensional finite element simulation model according to the geological survey data,discusses the seepage situation of each excavation stage before and after adding curtain and with different lateral curtain width in detail,and analyzes the relationship between lateral curtain width and levee and foundation pit.The results show that:The seepage gradient of the two corners of the foundation pit near the levee is the largest without curtain,and the seepage damage is easy to occur near the two corners;The seepage gradient at the bottom of the intermediate curtain will slightly increase with the increase of the lateral curtain width;From the technical and economic point of view,the seepage prevention effect is obvious when the lateral curtain width is 17 m;The seepage gradient at the bottom of the intermediate curtain and at the end of the lateral curtain is large which should be paid close attention to.The research results provide an empirical reference for similar projects.